Increased expression of antimüllerian hormone and its receptor in endometriosis - Carrarelli, Patrizia; Rocha, Ana Luiza Lunardi; Belmonte, Giuseppe; Zupi, Errico; Abrão, Mauricio Simoẽs; Arcuri, Felice; Piomboni, Paola; Petraglia, Felice (Fertility and sterility, 2014)
To evaluate antimüllerian hormone (AMH) and AMH receptor II (AMHRII) mRNA and protein expression in endometrium and in ovarian or deep lesions of women with endometriosis. Prospective study. University hospitals in Italy and Brazil. Patients with endometriosis (n = 55) and healthy women (n = 45). Specimens of endometrium obtained by hysteroscopy from patients with endometriosis and from healthy control subjects; specimens of ovarian endometriosis (n = 29) or of deep endometriosis (n = 26) were collected by laparoscopy. Serum samples were collected in some endometriotic patients (n = 23) and healthy control subjects (n = 20). AMH and AMHRII mRNA levels were evaluated by quantitative reverse-transcription polymerase chain reaction and protein localization by immunohistochemistry. AMH levels in tissue homogenates and in serum were assessed by ELISA. Endometrium from women with endometriosis showed higher AMH and AMHRII mRNA levels than control women, with no significant differences between proliferative and secretory phases. Specimens collected from ovarian or deep endometriosis showed the highest AMH and AMHRII mRNA expression. Immunolocalization study confirmed the high AMH and AMHRII protein expression in endometriotic lesions. No difference of serum AMH levels between the groups was found. The increased AMH and AMHRII mRNA and protein expression in endometrium and in endometriotic lesions suggests a possible involvement of AMH in endometriosis.